School Setting in Realizing Effective Schools (Case Study in Behavioristic Perspective at SMPN 3 Darangdan) - Heri Hasanudin; Iis Kurniawati K; Suharyanto Soro; Nana Herdiana Abdul Rahman (Global Education Journal, 2025)
Effective schools are still limited in number and these schools are an indicator of the success of the implementation of education which is not only determined by academic achievements, but also by the formation of disciplinary behavior and learning culture of students. One of the strategic factors that plays a role in realizing an effective school is the school setting, which is the management of the school environment which includes physical, social, academic, and cultural aspects of the school. In a behavioristic perspective, the school environment is understood as a series of stimuli that systematically shape students' behavioral responses through reinforcement mechanisms. This study aims to analyze the application of school setting in realizing effective schools in SMP Negeri 3 Darangdan through a behavioristic perspective. This research uses a qualitative research paradigm with a case study approach. Data collection was carried out through non-participatory observation, in-depth interviews, and documentation studies on school rules and habituation programs. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawing by applying triangulation of sources and techniques to maintain the validity of the data. The results of the study show that the school setting at SMP Negeri 3 Darangdan is implemented through the management of an orderly physical environment, the implementation of clear school rules, discipline habituation, and a relatively consistent educational reward and sanction system. In a behavioristic perspective, rules and rules function as a stimulus, while rewards and sanctions act as behavioral reinforcement. The conclusion of the study is that the implementation of the school setting contributes positively to the formation of student discipline behavior, a positive learning culture, and a conducive school climate.